Assessment of Water Quality Status Using Univariate Analysis at Klang and Juru River, Malaysia - Hafizan, Juahir; Mohd Saupi, Mohd Zin; Mohd Khairul Amri, Kamarudin; Azman, Azid; Noorjima, Abd Wahab (2017)
Klang River and Juru River which today suffers from water quality problems resulting from anthropogenic and geomorphology factors. The purpose of this study was to assess the water quality status from 2009 until 2013. 10 monitoring stations covering along Klang River and Juru River were selected.Six water quality parameters analyzed based on in-situ and ex-situ analysis were carried out according to the univariate analysis to obtain WQI level. The result indicated the impact of various anthropogenic and geomorphology activities contributed higher values of BOD, COD, SS and NH3-NL but the TSS concentration contamination at Juru River still on stable condition. Downstream and middle stream more polluted than upstream area triggered by pollutants from waste products of development activities,which inclusion of a high amount of pollutants of Klan River and Juru River.